Use of the local energy resource in the El Carmen canton of the Manabí province - Pérez, Antonio Vázquez; Ramos, Jorge Líder Macias; Gámez, María Rodríguez; Giler, Beatriz Irene Caballero; Villavicencio, Cesar Ivan Palma; Mendoza, Marjory Elizabeth Caballero (Linguistics and Culture Review, 2021)
The supply of energy to the entire Ecuadorian population constitutes a great challenge for the country, especially in rural areas where it is more difficult and expensive to extend the lines of the electricity system and where, despite efforts, the required quality of service is not achieved. presenting a negative impact on meeting the needs and socioeconomic development of rural regions. The objective of the research is to study the hydraulic potential of the De Oro River, for which 12 communities were visualized that are close to the riverbed and where technologies capable of taking advantage of the small existing potential in terms of improving quality could be used. electricity service, save natural resources and contribute to the reduction of CO2 emissions into the atmosphere. Data series are presented in tables that allow to analyze the result of the study of the hydraulic potential in 12 river sites and its possible link in terms of benefiting the social element that resides near these points, the field study was implemented as a methodology.